International Hospitality Management / Concepts and Cases - Chen Wei; Clark Alan (Elsevier, 2007)
This book brings together the latest developments in global hospitality operations with contemporary management principles. Preface, Acknowledgements, Welcome: An Introduction to International Hospitality, Cultures and the Challenges of International Hospitality, The International Hospitality Industry, Exploring the International Environment, International Marketing, International Hospitality Market Entry, Strategic Planning and International Hospitality, International Human Resources Management: Managing Diversity, Entrepreneurship and SMEs in the Global Market, Managing Social Responsibility in International Hospitality, The Analysis of International Hospitality Management, Bibliography and References, Author and Subject Index.